MAKNA LANGGAM PENDAPA AGENG PURI MANGKUNEGARAN SURAKARTA - ENY KRISNAWATI (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2001)
Form of tradional architecture are not only visible things, but also the symbolic meaning that are contained in them. The meaning in architecture has an important role for architectural form. The design of bulding and the form of bulding have the strong relation with the special element of culture and have relation with condition of nature (Amos Rapoport, 1976). Style is the appearning charaeteristic in object, designed as aresult of using special form. Style has relation with the charaeteristic of building fisically. Puri Mangkunegaraan was built in 1725 by K.G.P.A.A. Mangkunegara I or raden Mas said or Pangeran Samber Nyawa. Puri Mangkunegaran was built in concept of Javanese traditional architecture, with all tre form and symbols which have the special meaning, form the conceptof design, orientation, the form till the style that had syimbolic meaning, all of those come to saved and prosperous condition fisically and soully. The Pendapa is one ofÂ parts of the complex of Javanise traditional building that have concept and meaning basides the Peringgitan and dalem Ageng buildings. Pendapa in Javanese traditional house are used as public building, guest room, and room for the spectator who attendÂ the shadow puppet held in Peringgitan building. Pendapa Mangkunegaran is the biggest one of some building in indonesia that have many symbols in its architecture. With this background the seacher would like to analize the meaning of the style contained in Pendapa Ageng Mangkunegaran. Along with the aim of the search, that is qualitativdescriptive search, so the approach of description is to be used combined with the picturial media and theories.